Cross-cultural differences in the acceptance of decisions of automated vehicles. (April 2021) - Edelmann, Aaron; Stümper, Stefan; Petzoldt, Tibor
Abstract: Automated vehicles are expected to enhance driving safety and comfort. In order to fulfil these expectations, they have to be widely accepted and used. Implementing an acceptable driving style is therefore a must. Previous research on automated vehicle acceptance has largely concentrated on the effects of driving dynamics. This study takes a different approach and focuses on the effects of the driving decisions. To assess the effects of driving decisions on acceptance, an online experimental study was conducted in China, Germany, Japan and the US. Four overtaking scenarios, in which the automated vehicle took a decision, were presented as short texts. The situations differed with regard to the action (overtaking vs. stay in lane) and potential consequence (high or low hindrance of another driver). Participants then rated their acceptance. The results indicate that acceptance is dependent on the driving decisions and is further influenced by cultural background. Chinese drivers show high acceptance to the decisions and there were no significant differences between the presented scenarios. In the US and Germany, decisions leading to high hindrance of others are rejected, whereas in cases of low hindrance, overtaking is preferred. Japanese participants reject decisions, which lead to hindrance of others. Highlights: Culture influences the acceptance of overtaking manoeuvres of an automated vehicle. Japanese users prefer staying in lane regardless of degree of hindrance. Chinese drivers show higher acceptance for overtaking compared to staying in lane. German and US participants want automated vehicle to overtake if hindrance is low.